2014
DOI: 10.1055/s-0034-1379032
|View full text |Cite
|
Sign up to set email alerts
|

Mild and Selective Deprotection of tert-Butyl(dimethyl)silyl Ethers with Catalytic­ Amounts of Sodium Tetrachloroaurate(III) Dihydrate

Abstract: A simple and mild method for the removal of tert-butyl(dimethyl)silyl (TBS) protecting groups with catalytic amounts of sodium tetrachloroaurate(III) dihydrate is described. The procedure permits selective deprotection of aliphatic TBS ethers in good to excellent yields in the presence of aromatic TBS ethers, aliphatic triisopropylsilyl ethers, aliphatic tert-butyl(diphenyl)silyl ethers, or sterically hindered aliphatic TBS ethers. Additionally, TBS ethers can also be transformed into 4-methoxybenzyl ethers or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…21 Catalytic NaAuCl 4 •2H 2 O in MeOH has been used to deprotect four phenolic TBDMS groups, but the method gave a low yield with an electron-deficient phenol. 22 In connection with ongoing work on desilylations of some nucleoside substrates, we found the compounds to be exceptionally sensitive to a variety of conventional fluoride reagents. This necessitated the evaluation of alternate reagents and we have found that KHF 2 in MeOH is a mild reagent for cleavage of phenolic TBDMS groups.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…21 Catalytic NaAuCl 4 •2H 2 O in MeOH has been used to deprotect four phenolic TBDMS groups, but the method gave a low yield with an electron-deficient phenol. 22 In connection with ongoing work on desilylations of some nucleoside substrates, we found the compounds to be exceptionally sensitive to a variety of conventional fluoride reagents. This necessitated the evaluation of alternate reagents and we have found that KHF 2 in MeOH is a mild reagent for cleavage of phenolic TBDMS groups.…”
mentioning
confidence: 88%
“…21 Catalytic NaAuCl 4 ·2H 2 O in MeOH has been used to deprotect four phenolic TBDMS groups, but the method gave a low yield with an electron deficient phenol. 22 …”
mentioning
confidence: 99%
“…Generally, 0.1 mol% Hf(OTf) 4 was ideal to selectively remove 1°a lkyl TBS ether in the presence of 2°, 3° alkyl and aryl TBS ethers. However, the presence of other functional groups such as carbamate (20,21,24) required elevated amounts of Hf(OTf) 4 for regioselective removal of 1° or 2° alkyl TBS ether. As an extension of this method, the 5′-O-TBS of fully TBS protected uridine (25) and thymidine (26) was smoothly and selectively removed in high yield with 0.5 mol% Hf(OTf) 4 .…”
Section: Table 2 Effect Of Hf(otf) 4 Amount On Tbs Deprotectionmentioning
confidence: 99%
“…Compounds 1-46 were prepared according to methods described in the literature. 1,2,21 All reactions were monitored by TLC on plates coated with 0.25 mm silica gel 60 F 254 . TLC plates were visualized by UV irradiation (254 nm) or staining with p-anisaldehyde.…”
Section: Paper Syn Thesismentioning
confidence: 99%
See 1 more Smart Citation